A Novel Expression Domain of extradenticle Underlies the Evolutionary Developmental Origin of the Chelicerate Patella - Klementz, Benjamin C (2024)
Neofunctionalization of duplicated gene copies is thought to be an important process underlying the origin of evolutionary novelty and provides an elegant mechanism for the origin of new phenotypic traits. One putative case where a new gene copy has been linked to a novel morphological trait is the origin of the arachnid patella, a taxonomically restricted leg segment. In spiders, the origin of this segment has been linked to the origin of the paralog dachshund-2, suggesting that a new gene facilitated the expression of a new trait. However, various arachnid groups that possess patellae do not have a copy of dachshund-2, disfavoring the direct link between gene origin and trait origin. We investigated the developmental genetic basis for patellar patterning in the harvestman Phalangium opilio, which lacks dachshund-2. Here, we show that the harvestman patella is established by a novel expression domain of the transcription factor extradenticle. Leveraging this definition of patellar identity, we surveyed targeted groups across chelicerate phylogeny to assess when this trait evolved. We show that a patellar homolog is present in Pycnogonida (sea spiders) and various arachnid orders, suggesting a single origin of the patella in the ancestor of Chelicerata. A potential loss of the patella is observed in Ixodida. Our results suggest that the modification of an ancient gene, rather than the neofunctionalization of a new gene copy, underlies the origin of the patella. Broadly, this work underscores the value of comparative data and broad taxonomic sampling when testing hypotheses in evolutionary developmental biology.